What is the effect of electronic health records on malpractice claims?. Issue 4 (April 2017) - Kirsch, Caroline; Melville, Brian Tyler
Abstract : EVIDENCE‐BASED ANSWER : The use of electronic health records (EHRs) does not appear to effect the frequency of malpractice claims made or the frequency of malpractice claims paid (SOR: C, retrospective cohort and cross‐sectional studies).